Knowledge, Attitude, and Practice of Dog Owners on Rabies In The Province of West Java - Dinda Devira; Tyagita .; Helni Mariani (Jurnal Sain Veteriner, 2023)
West Java Province is one of the regions that is still not rabies-free. Although the ISIKHNAS data shows that West Java had no rabies cases in 2021, there were 313 cases of bites by Rabies Transmitting Animals reported, so the public needs to remain vigilant against rabies. This study aims to determine and analyze the dog owner's level of knowledge, attitude, and practice regarding rabies. The research was conducted using a survey method (questionnaire) using a Google form which was distributed via social media and was filled in by 108 respondents from various regions in West Java in October-November 2022. The questionnaire in this study was the result of a modification from previous research in Sukabumi Regency and is valid and reliable based on test results to 30 respondents outside the research sample. The research data were then processed descriptively. The study's findings revealed that most of the respondents (43.5%) have sufficient level of knowledge, positive attitude level (89.8%) and good practice level (84.3%). There is some knowledge that has not been obtained properly, especially in the information that there is no effective drug to cure rabies. The findings of this study may provide the foundational information for future research and help to identify the kinds of interventions and programs that can be put in place to prevent and reduce rabies cases throughout all study locations.